Sex-Specific Differences in the Effect of Free Testosterone on Sarcopenia Components in Older Adults - Shin, Hyung Eun; Walston, Jeremy D.; Kim, Miji; Won, Chang Won (Frontiers in Endocrinology, 2021)
Objective: The association of free testosterone (FT) with sarcopenia and its components is well known in men but incompletely understood in women. We examined the association of baseline FT with prevalent and incident sarcopenia and its components in community-dwelling older adults. Design: Cross-sectional and longitudinal analysis from the prospective population-based Korean Frailty and Aging Cohort Study. Methods: A total of 1,879 community-dwelling older adults aged 70–84 years were enrolled for cross-sectional analysis and 1,583 subjects who participated in the 2-year follow-up survey were included for longitudinal analysis. Baseline FT levels was measured by radioimmunoassay. Skeletal muscle mass, handgrip strength, and physical performance tests were measured at baseline and after 2-year follow-up. Sarcopenia was defined by the diagnostic criteria of the Asian Working Group for Sarcopenia (AWGS). Results: Continuous FT levels was positively associated with prevalent sarcopenia in men (odds ratio [OR]=0.95; 95% confidence interval [CI]=0.89–1.00)] and women (OR=0.64, 95% CI=0.42–0.99) after adjusting for multiple confounders. In prospective analysis, low FT levels was associated with a decrease in handgrip strength in women (β=-0.61; p=0.010) and a reduction in Timed “Up and Go” (TUG) test (β=0.53; p=0.008) in men after 2 years. No significant correlations were found between FT levels and incident sarcopenia. Conclusions: Low levels of FT may be a significant determinant of decreases in muscle strength in women and declines in physical performance in men after 2 years. Low FT do not predict loss of muscle mass in both men and women.